Defending Neutrality: The Netherlands Prepares for War, 1900-1925 - Klinkert, Wim (History of Warfare, 2013)
Defending Neutrality analyses the broad spectrum of war preparation of a small neutral state, The Netherlands, before, during and after the First World War. It deals with the role of neutral states close to the front and with the internal technological, military and societal developments within that state to ensure its survival.